2014
DOI: 10.2500/ajra.2014.28.3962
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Molecules as Predictors of Nasal Polyposis Recurrence

Abstract: Adhesion molecules may relate to nasal polyp prognosis and recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Further attempts should be made to go beyond clinical and conventional pathological considerations and investigate the biological mechanisms behind CRSwNP. Since molecular changes are primarily responsible for the biological behavior of inflammation, new biomarkers involved in angiogenesis [20], proliferation, adhesion molecules [24], and tissue remodeling have to be tested by immunohistochemistry and/or quantitative real-time polymerase chain reaction to see if they can help in predicting the course of CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…Further attempts should be made to go beyond clinical and conventional pathological considerations and investigate the biological mechanisms behind CRSwNP. Since molecular changes are primarily responsible for the biological behavior of inflammation, new biomarkers involved in angiogenesis [20], proliferation, adhesion molecules [24], and tissue remodeling have to be tested by immunohistochemistry and/or quantitative real-time polymerase chain reaction to see if they can help in predicting the course of CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that nasal polyps recur in approximately one‐third of patients after surgical treatment, CRSwNP phenotypes would be helpful in depicting patients in whom we might expect recurrence and in predicting clinical outcome after surgery. Significant efforts have been made to individuate some specific clinical (comorbid asthma), serological (high peripheral eosinophil count and histological predictors of recurrence, such as high eosinophilic infiltrates in polyps and adhesion molecules (mucin 1 and CD86 stromal expression): Wormald and colleagues recommended that the extent of mucosal inflammatory load, especially tissue eosinophils, should be considered as the most important indicator for functional or radical surgical approach . Similarly, Uhliarova et al demonstrated that in patients with CRSwNP and elevated levels of eosinophils in the nasal lavage fluid and in nasal tissue are significantly more prone to recurrence and therefore require higher rate of revision FESS (Functional Endoscopic Sinus Surgery).…”
Section: Chronic Rhinusinusitis With and Without Nasal Polypsmentioning
confidence: 99%
“…Factors such as symptom severity, preoperative computed tomography (CT) score, polyp size, comorbid asthma, allergic status, peripheral eosinophilia, adhesion molecules expression, and mucosal histologic characteristics shed light on the association with polyp recurrence in previous studies. [11][12][13][14][15][16][17] Among these parameters, mucosal eosinophilia is a more important predictor than other predictors. 4,13 However, mucosal eosinophilia exhibits significant geographic and ethnic differences.…”
mentioning
confidence: 99%